2001
DOI: 10.1119/1.1343420
|View full text |Cite
|
Sign up to set email alerts
|

Using wireless keypads in lecture classes

Abstract: about 50% across disciplines. Blame for this unfortunate loss of students was most often attributed to the large, impersonal lecture format rather than to the subject being taught. We wanted to improve the lecture experience by actively involving the students more in the lecture itself. Reasons for the reluctance of students to respond in a large lecture were understandable. Recent articles by Hake 2 and Poulis 3 furnish data to support our approach and have established the value of modifying the passive lectu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
90
0
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(99 citation statements)
references
References 12 publications
5
90
0
4
Order By: Relevance
“…An example of one of these failures was due to the set-up of the room obstructing the technology, rendering some students unable to respond to the questions asked using LAP. 45,50 However, it has also been shown that most objections to the use of interactive learning devices occur during the initial period of implementation, perhaps before the initial flaws are rectified. 9 As figure 2 demonstrates there were fewer responses using LAP in the first lecture (questions 1-4) which may highlight the initial reluctance to engage in a new system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An example of one of these failures was due to the set-up of the room obstructing the technology, rendering some students unable to respond to the questions asked using LAP. 45,50 However, it has also been shown that most objections to the use of interactive learning devices occur during the initial period of implementation, perhaps before the initial flaws are rectified. 9 As figure 2 demonstrates there were fewer responses using LAP in the first lecture (questions 1-4) which may highlight the initial reluctance to engage in a new system.…”
Section: Discussionmentioning
confidence: 99%
“…A further affirmative characteristic of the use of LAP has been highlighted in the literature; the use of LAP in teaching sessions resulted in improved attendance. 9,11,39,40,46,50,53,62 It would be idealistic to imagine that this technology, whilst it has its benefits, does not come without some obstacles. Arguably the most important of these is the issue of cost.…”
Section: Effects Of Lap On the Institutionmentioning
confidence: 99%
“…This not only helps students develop the interactive and critical thinking skills that are so important for their development as scientists, but also allows them to address any conceptual or reasoning difficulties before they become firmly ingrained in a student's cognitive structure and, therefore, resistant to correction [15]. In addition, Burnstein and Lederman [16] showed that the use of a PRS increased student attendance, kept them more alert during class, and improved their overall performance and motivation for learning.…”
Section: Summative Assessment: Measuring (Grading)mentioning
confidence: 99%
“…The resulting distribution can then be presented graphically to the class via a data projector to support assessment, discussions, group activities, etc. Replacing or supplementing the traditional lecture and note-taking classes (passive learning) with this type of interactive process appears to support learning by increasing productive communication of processes, understandings and ideas and encouraging student engagement (Horowitz, 1988;Burnstein & Lederman, 2001;Guthrie & Carlin, 2004;Pelton and Francis Pelton, 2003;.…”
Section: Introductionmentioning
confidence: 99%